1998
DOI: 10.1145/280549.280555
|View full text |Cite
|
Sign up to set email alerts
|

On routes and multicast trees in the Internet

Abstract: Multicasting has an increasing importancefor network applications such as groupware or videoconferencing. Several multicast routing protocols have been defined. However they cannot be used directly in the Internet since most inter-domain routers do no implement multicasting. Thus these protocols are mainly tested either on a small scale inside a domain, or through the Mbon~, whose topology is not really the same as Internet topology. The purpose of this paper is to construct a graph using actual routes of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(132 citation statements)
references
References 5 publications
4
127
0
1
Order By: Relevance
“…On the router level, according to relatively poor data from 1995 [5,106], the Internet consisted of 3888 vertices and 5012 edges, with the average degree equal to 2.57 and the maximal degree equal to 39. The degree distribution of this network was fitted by a power-law dependence with the exponent, γ ≈ 2.5.…”
Section: Structure Of the Internetmentioning
confidence: 99%
“…On the router level, according to relatively poor data from 1995 [5,106], the Internet consisted of 3888 vertices and 5012 edges, with the average degree equal to 2.57 and the maximal degree equal to 39. The degree distribution of this network was fitted by a power-law dependence with the exponent, γ ≈ 2.5.…”
Section: Structure Of the Internetmentioning
confidence: 99%
“…This reduction improves the scalability of the protocol. Note that, this result is in agreement with the results presented in [6,11], which reports that close to 70% of the nodes in a tree are non-branch nodes and only function as traffic relay nodes.…”
Section: Evaluating Large Scale Deployment Of Menusupporting
confidence: 92%
“…Firstly, the scalability of any protocol which stores state in the core of the network may be poor. Secondly, research findings [6,11] have shown that close to 70% of nodes in multicast trees have average an fanout degree of 2 and only function as traffic relay nodes, i.e. performing vanilla packet forwarding as in conventional IP.…”
Section: Menu Protocol Conceptmentioning
confidence: 99%
“…Measurement points are deployed on the PlanetLab testbed and the network is daily probed (traceroute probing). The obtained data is then postprocessed in order to provide finer grained information, such as router level topology (the alias resolution techniques used are DNS based [6] and address-based [29], [30]), IPto-AS mapping, IP-to-PoP mapping, bandwidth estimation, etc. Discarte [31] is an example of a new scalable probing technique that relies on existing techniques.…”
Section: Disconnected Componentsmentioning
confidence: 99%